Determinism on Hume´s philosophy: A perspective from naturalism - Vargas Abarca, Mauricio (2025)
This research explores the concepts of causality, necessary connection, and probability in Hume’s philosophy, with the aim of showing how, from a naturalistic perspective and the regularity in impressions (custom), the Scottish philosopher cannot be considered a radical skeptic, as has often been interpreted.  His skepticism only challenges reason as the foundation of causality and necessary connection, but he does not doubt the truth of these relations or their epistemological significance in the construction of positive knowledge of reality.